Study, synthesis nickel hydroxide thin film by electrochemical method and several factors influence on its structure and electrochemical properties - Viet, Nguyen Xuan; Sen, Trinh Xuan; Cam Ha, Nguyen Thi (Vietnam Journal of Chemistry, 2012)
The aim of this work was to study the influence of the concentration Ni(NO3)2 precursor, current density and deposited time on the structure and the electrochemical properties corresponding with nickel hydroxide thin films preparing by the electrochemically deposited method. The results indicated that these films were the α-Ni(OH)2 form and the film was electrodeposited at 3 mA/cm2, 300 seconds in 0.001 M Ni(NO3)2 solution shows the best electrochemical properties.